DNA-Functionalized 100 nm Polymer Nanoparticles from Block Copolymer Micelles - Lee, Saerom; Yoon, Jeong Hoon; Jo, In Seong; Oh, Joon Suk; Pine, David J.; Shim, Tae Soup; Yi, Gi Ra (Langmuir, 2018)
DNA-mediated self-assembly of colloidal particles is one of the most promising approaches for constructing colloidal superstructures. For nanophotonic materials and devices, DNA-functionalized colloids with diameters of around 100 nm are essential building blocks. Here, we demonstrate a strategy for synthesizing DNA-functionalized polymer nanoparticles (DNA-polyNPs) in the size range of 55-150 nm using block copolymer micelles as a template. Diblock copolymers of polystyrene-b-poly(ethylene oxide) with an azide end group (PS-b-PEO-N3) are first formed into spherical micelles. Then, the micelle cores are swollen with the styrene monomer and polymerized, thus producing PS NPs with PEO brushes and azide functional end groups. DNA strands are conjugated onto the ends of the PEO brushes through a strain-promoted alkyne-azide cycloaddition reaction, resulting in a DNA density of more than one DNA strand per 12.6 nm2 for 70 nm particles. The DNA-polyNPs with complementary sequences enable the formation of CsCl-type colloidal superstructure by DNA binding.
Keywords: Block co-polymer micelles; Colloidal particle; Complementary sequences; Cycloaddition reaction; Functional end groups; Functionalized polymers; Nanophotonic materials; Polymer nanoparticles; Alkynes; Azides; Colloids; Cycloaddition Reaction; DNA; Micelles; Nanoparticles; Particle Size; Polyethylene Glycols; Polymerization; Polystyrenes